PROBLEMS OF COMPREHENSIVE TREATMENT OF CONGENITAL DEFECTS WITH URINARY INCONTINENCE IN CHILDREN. (World Bulletin of Public Health, 2024)
Today, 11.3% of newborns are born with various deviations from the norm of development, and more than 40% of them are caused by insufficiency and anomalies of the genitourinary system (Yu.F. Isakov, 1984; 1997; 2004: G.A. Bairov 1999; 2001, etc.). Among them, deviations from the norm complicated by urinary incontinence account for 8.0%. Complex treatment of developmental defects caused by urinary incontinence in children has long attracted the attention of practicing surgeons. and today is one of the most pressing problems of pediatric surgery. (N.E. Savchenko, 1976 edition: A.E. Rusakov 1998; Yu. Beknazarov 2004, etc.).